Reformulation of Consumer Protection Law Regulations as an Effort to Enforce Justice in e-Commerce Transactions in Indonesia - Rohmah, Firda Nur; Karim, Moh (Universitas Trunojoyo Madura, 2025)
The development of business is currently increasingly rapid, in addition to the development of technology is also increasingly rapid, so the development of law must also follow the times. Currently in Indonesia there have been various kinds of transactions from face-to-face transactions to online transactions. This does not deny that there will be legal problems that occur. To anticipate this from happening, the government has issued Law Number 8 of 1999 (UUPK) concerning consumer protection. On the other hand, e-commerce transactions make it easier for consumers to meet their needs without having to go far, all needs can be met just by sitting back at home. Therefore, interest in e-commerce is increasing, but it is undeniable that there is also a lot of fraud committed by the parties. The research uses a comparative method with a qualitative approach. Data was collected throught interviews with 10 respondents (costumers and e-commerce business actors) as well as analysis of custumer protection regulatory documents. The research result show a significant gap between theory and practice, especially in terms of customer and business awareness, as well as a lack of effective regulation. The research concludes that it is necessary to improve regulations, increase consumer and business awareness, and develop human resources. The implications of this research can be used as a reference for developing e-commerce consumer protections policies that are more effective and protect consumer rights. This research contributes to the development of consumer protection theory in the context of e-commerce.